Nanoparticles as a Tool in Neuro-Oncology Theranostics - Andrea L. Klein; Grant Nugent; John Cavendish; Werner J. Geldenhuys; Krishnan Sriram; Dale Porter; Ross Fladeland; Paul R. Lockman; Jonathan H. Sherman (MDPI AG, 2021)
The rapid growth of nanotechnology and the development of novel nanomaterials with unique physicochemical characteristics provides potential for the utility of nanomaterials in theranostics, including neuroimaging, for identifying neurodegenerative changes or central nervous system malignancy. Here we present a systematic and thorough review of the current evidence pertaining to the imaging characteristics of various nanomaterials, their associated toxicity profiles, and mechanisms for enhancing tropism in an effort to demonstrate the utility of nanoparticles as an imaging tool in neuro-oncology. Particular attention is given to carbon-based and metal oxide nanoparticles and their theranostic utility in MRI, CT, photoacoustic imaging, PET imaging, fluorescent and NIR fluorescent imaging, and SPECT imaging.